(untitled) (Linguostylistic Studies, 2023)
The study highlights the issue of the development of the communicative competence of civil servants, heads of local state administrations, their first deputies and assistants, officials of local self-government, and local council deputies. The study focuses on the dynamics of advanced training programs offered for the continuous personal and professional development of persons authorized to perform the functions of the state and local self-government in the professional training system, the priority directions (topics) of which are: ways to improve the mastery level of the Ukrainian business language, communication and interaction, strategic communications, etc. The analysis is carried out on the case study materials of the Volyn Regional Center for Professional Development (formerly the Volyn Regional Center for Retraining and Professional Development of employees of state and local self-government bodies, state enterprises, institutions, and organizations). The author has considerable experience in cooperation with the Center from 2008 to 2023, in particular in the field of development and implementation of general and special short-term advanced professional training programs. Emphasis is laid on the need for more active implementation of distance learning technologies in the organization of the educational process, which is not limited to telecommunication. The study elucidates the specifics and content dominants of training programs for professional development in the context of the main aspects of language and communication activities of public servants at the beginning of the 21st century: work with documents (in particular, in the electronic document management system), the ability to conduct interpersonal and social dialogue (especially with the use of media), taking into account the principles of barrier-free communication, and the ability to speak in public. The study findings made it possible to design innovative programs/projects for the development of the communicative competence of public servants, which were developed following the principle of the practical orientation of training, taking into account military-political, social, and economic factors, as well as the individual needs of training participants (according to questionnaires), in particular, in conditions of martial law and post-war period.